2012
DOI: 10.1177/1078087411432418
|View full text |Cite
|
Sign up to set email alerts
|

What Determines the Formal Versus Relational Nature of Local Government Contracting?

Abstract: In this article, we examine the governance structures used to manage local service delivery contracts with an eye toward two specific concerns. First, we contend that public managers likely use dual regimes in which contract writing is more formal in nature than is the management style adopted during contract implementation. We also explore the determinants of such mechanisms. We find some evidence to support our contention in that managers frequently contact and communicate with their vendors despite the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 54 publications
0
16
0
1
Order By: Relevance
“…Although this negative expectation is well grounded, there is also a considerable literature claiming that the effects of outsourcing are conditional, pointing to the buyer's management capacity as one of the most salient conditioning factors (Romzek and Johnston ; Van Slyke ; Brown et al , ). Specifically, it was found that the quality of management‐level personnel matters when it comes to selecting the most suitable provider (Romzek and Johnston ) and contract drafting, monitoring the contract's performance (Kettle ; Brown and Potoski ; Van Slyke ), and adjusting its implementation (Van Slyke ; Amirkhanyan ; Brown et al ; Lamothe and Lamothe ). As Van Slyke (, p. 296) put it, ‘To reap the benefits of competition, government must be a smart buyer, a skilful purchasing agent, and a sophisticated inspector of the goods and services it purchases from the private sector.’…”
Section: Theoretical Argument: Outsourcing Bureaucratic Personnel Qumentioning
confidence: 99%
“…Although this negative expectation is well grounded, there is also a considerable literature claiming that the effects of outsourcing are conditional, pointing to the buyer's management capacity as one of the most salient conditioning factors (Romzek and Johnston ; Van Slyke ; Brown et al , ). Specifically, it was found that the quality of management‐level personnel matters when it comes to selecting the most suitable provider (Romzek and Johnston ) and contract drafting, monitoring the contract's performance (Kettle ; Brown and Potoski ; Van Slyke ), and adjusting its implementation (Van Slyke ; Amirkhanyan ; Brown et al ; Lamothe and Lamothe ). As Van Slyke (, p. 296) put it, ‘To reap the benefits of competition, government must be a smart buyer, a skilful purchasing agent, and a sophisticated inspector of the goods and services it purchases from the private sector.’…”
Section: Theoretical Argument: Outsourcing Bureaucratic Personnel Qumentioning
confidence: 99%
“…Our measures of product characteristics are derivative of well-established measures in the extant literature (Brown & Potoski, 2005;Lamothe & Lamothe, 2012;Levin & Tadelis, 2010). We followed the measurement scheme of Brown and Potoski (2005), with some important improvements.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Second, we produce unique measures of product characteristics that are not currently available in the literature. Past research on product characteristics at the local level has proved useful to many scholars interested in the dynamics of local government contracting (e.g., Brown & Potoski, 2005;Lamothe & Lamothe, 2012;Levin & Tadelis, 2010). We provide measures that can be used by scholars undertaking similar research at the federal level.…”
mentioning
confidence: 99%
“…Thus, the case of the IFSCs in Guangzhou has illustrated that the service agreements and the independence of NGOs need to be legally protected by the administrative orders and laws of central government. This means that the Chinese government’s service contracts with NGOs need to be ‘detailed, binding legal agreements that specify the obligations and roles of both parties in the relationship’ (Vandaele et al, 2007, quoted in Lamothe and Lamothe, 2012: 324). This type of contract helps protect ‘the rights and properties of potentially opportunistic participants’ (p. 324).…”
Section: Discussionmentioning
confidence: 99%